HUBUNGAN POLA ASUH ORANG TUA DAN TINGKAT ASUPAN NUTRISI DENGAN RESIKO TERJADINYA BGM (BAWAH GARIS MERAH) DI WILAYAH KERJA PUSKESMAS KETAWANG - Susana Setyowati, Susana Setyowati; Ariani, Ariani (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
Nutritional status for children under five can be seen with the KMS book. In children with poor nutritional status, it will be indicated by a red line. The nutritional status of these children is influenced by economic conditions, level of knowledge and parenting.This study aims to determine the relationship between parenting and the level of nutritional intake with the risk of BGM carried out in January-March 2018, with quantitative methods, a sample of 86 respondents and methods of data collection using interviews, questionnaires and documentation. The collected data was analyzed using statistical analysis multiple linear regression methods.Statistical analysis shows that parenting variables (X1) thitung2.707> t0.05 prove that there is a significant relationship to the risk of BGM (Y). Variable level of nutrient intake (X2) has a value of 4.004 > t 0.05 proving that there is a significant relationship to the risk of BGM (Y). And the calculated F-value is 45,658 > F-table (0.05), the research hypothesis is proven that parenting (X1), nutrient intake level (X2) with the occurrence of BGM (Y). R2 (R-square) value is 0.0524 or 52.45%. This shows that the percentage of the influence of the independent variables of parenting (X1) and the level of nutrient intake (X2) on the dependent variable risk of the occurrence of BGM (Y) is 52.45%. While the rest is 51.6% influenced by factors or other variables not included in this study. Of the two independent variables (X) it is known that the more dominant variable is Y (BGM) is X2 (level of nutrient intake) with a value of t-count > t-table 4.004 > 2.000.Parenting and nutritional intake are related to BGM. It is recommended that parents always pay attention to and accompany the child so that adequate nutritional intake.